2011
DOI: 10.1159/000321212
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Umbilical Cord in Preeclampsia

Abstract: Objectives: To investigate the role of biochemical changes in the umbilical cord and placenta in developing preeclampsia (PE). Subjects and Methods: Thirty women with PE and 15 healthy pregnant women as controls were enrolled in this study. Vascular endothelial growth factor (VEGF), soluble vascular endothelial growth factor receptor 1 (sVEGFR-1), platelet-derived endothelial cell growth factor (PD-ECGF), neutrophil elastase and nitric oxide (NO) were measured. Results: Both serum (maternal and fetal) and tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
2
2
1
Order By: Relevance
“…Another study reporting results that differ from the present research has found higher sFlt-1 and sEng levels in early-onset compared to late-onset pre-eclampsia but no significant difference in PIGF levels, again agreeing with the results reported here [19]. Salama et al have produced a similar to the present researchers' but have divided the pre-eclampsia group into mild and severe cases, arriving at a result similar to ours in that no difference was found between the two groups in terms of VEGF and sFlt-1 levels [31].…”
Section: Angiogenic and Anti-angiogenic Factors In Early-and Late-onssupporting
confidence: 92%
See 1 more Smart Citation
“…Another study reporting results that differ from the present research has found higher sFlt-1 and sEng levels in early-onset compared to late-onset pre-eclampsia but no significant difference in PIGF levels, again agreeing with the results reported here [19]. Salama et al have produced a similar to the present researchers' but have divided the pre-eclampsia group into mild and severe cases, arriving at a result similar to ours in that no difference was found between the two groups in terms of VEGF and sFlt-1 levels [31].…”
Section: Angiogenic and Anti-angiogenic Factors In Early-and Late-onssupporting
confidence: 92%
“…The results of research comparing angiogenic and anti-angiogenic factors in umbilical cord serum in preeclampsia are inconsistent. Some studies state that VEGF levels in the umbilical cord serum of pre-eclamptic patients are higher than in the control group [23,26,31]. Other results are similar to the findings in the present study and show that VEGF levels in the umbilical cord serum in the pre-eclampia group are lower than in the control group [24].…”
Section: Angiogenic and Anti-angiogenic Factors In Umbilical Cord Sersupporting
confidence: 90%
“…Sandrim et al detected lower levels of nitrite, an NO metabolite, in hypertensive and preeclamptic pregnancies than normal pregnancies and they suggested that NO synthesis is impaired in preeclampsia [19]. Salama et al, in their study of 30 preeclamptic and 15 normal pregnant women, reported lower levels of maternal and fetal blood NO levels in preeclamptic women in contrast to our results [20]. In Di Irorio et al's study, NO metabolite nitrate was found increased in amniotic fluid samples of preeclamptic women, however they had NO, nitric oxide.…”
Section: Discussioncontrasting
confidence: 91%
“…15 Elevated cord plasma VEGF levels have also been reported by others in women with PE. 48 Furthermore, Han et al 49 have reported no difference in cord plasma VEGF levels between PE and normotensive groups. In contrast to VEGF, we observed an increasing trend of cord plasma sFlt-1 levels in women with PE that is consistent with a number of earlier reports.…”
Section: Discussionmentioning
confidence: 99%